2016
DOI: 10.7567/jjap.55.052301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UV on power degradation of photovoltaic modules in combined acceleration tests

Abstract: UV exposure and other factors such as high/low temperature, humidity and mechanical stress have been reported to degrade photovoltaic (PV) module materials. By focusing on the combined effects of UV stress and moisture on PV modules, two new acceleration tests of light irradiation and damp heat (DH) were designed and conducted. The effects of UV exposure were validated through a change in irradiation time (UV dosage) and a change of the light irradiation side (glass side vs backsheet side) in the UV-preconditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…The VAc units are more vulnerable to heat, oxygen, and UV light radiation, and therefore could easily form reactive radicals or unstable hydroperoxides and thereby facilitate further irreversible chemical reactions. EVA photo-degradation has been reported to cause a number of degradation modes: It has been demonstrated that UV irradiation plays a significant role in generating acetic acid in the presence of relative humidity, which can cause corrosion and power degradation of PV modules [45].…”
Section: Aging Comparison: Decomposition Products From Ftir-atrmentioning
confidence: 99%
“…The VAc units are more vulnerable to heat, oxygen, and UV light radiation, and therefore could easily form reactive radicals or unstable hydroperoxides and thereby facilitate further irreversible chemical reactions. EVA photo-degradation has been reported to cause a number of degradation modes: It has been demonstrated that UV irradiation plays a significant role in generating acetic acid in the presence of relative humidity, which can cause corrosion and power degradation of PV modules [45].…”
Section: Aging Comparison: Decomposition Products From Ftir-atrmentioning
confidence: 99%
“…Pre‐exposure to light before PID testing has been shown to enhance the PID‐s effect in subsequently performed PID tests 15 . While the mechanism has not been clarified, it has been shown that exposure to UV light can lead to a subsequent increase the formation of acetic acid such as in damp heat, potentially promoting ionic conductivity 16 . On the other hand, a number of studies showed that the simultaneous application of light and system voltage results in a reduction of PID compared to the case without light for both PID‐p and PID‐s 5,17 .…”
Section: Introductionmentioning
confidence: 99%
“…15 While the mechanism has not been clarified, it has been shown that exposure to UV light can lead to a subsequent increase the formation of acetic acid such as in damp heat, potentially promoting ionic conductivity. 16 On the other hand, a number of studies showed that the simultaneous application of light and system voltage results in a reduction of PID compared to the case without light for both PID-p and PID-s. 5,17 This is attributable to annihilation of charge by the excitation of carriers from the incident high energy photons in the UV component of sunlight in the wide bandgap dielectrics used for passivating the silicon surface and also from the photoconductivity in the silicon nitride antireflective layer, reducing the electric field over the layer and the electromotive force for charge motion through it. 7 Considering the reports that PID-p can manifest in nonrepresentative dark ambient PID stress tests, it is of great importance to establish to what extent PID-p will occur in fielded modules where system voltage is accompanied by sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…We do not discuss the initial degradation and yearly degradation rates of performance in this paper. The degradation of front contact characteristics, which leads to an increase in series resistance, [11][12][13][14] and potentialinduced degradation (PID), which leads to a decrease in shunt resistance, [15][16][17] significantly affect the module lifetime. In this paper, some aspects of mechanism analyses of these degradation modes are described and the comparative experimental test results of the samples fabricated using conventional technology or our technology are also described.…”
Section: Introductionmentioning
confidence: 99%